Two new species and new records of Cerambycidae (Insecta, Coleoptera) from Itatiaia National Park, Rio de Janeiro, Brazil - Monné, Marcela L.; Monné, Miguel A.; Botero, Juan P.; Carelli, Allan (Zootaxa, 2016)
The descriptions of two species of Lamiinae, Lepturges (Lepturges) batesi sp. nov. (Acanthocinini) and Onocephala chicomendes sp. nov. (Onocephalini) and an addendum of Cerambycinae and Lamiinae to the list of species of Cerambycidae in the Itatiaia National Park are presented. The data are based on fieldwork conducted over the last six years. Eighteen species of Cerambycinae and 21 of Lamiinae are recorded, with a total of 39 new distribution records.